2021
DOI: 10.3390/ph14020133
|View full text |Cite
|
Sign up to set email alerts
|

Monofunctional Platinum(II) Anticancer Agents

Abstract: Platinum-based anticancer drugs represented by cisplatin play important roles in the treatment of various solid tumors. However, their applications are largely compromised by drug resistance and side effects. Much effort has been made to circumvent the drug resistance and general toxicity of these drugs. Among multifarious designs, monofunctional platinum(II) complexes with a general formula of [Pt(3A)Cl]+ (A: Ammonia or amine) stand out as a class of “non-traditional” anticancer agents hopeful to overcome the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 130 publications
0
30
0
Order By: Relevance
“…However, similar to all metal complexes, especially platinum drugs, they have disadvantages, the most troublesome of which is low bioavailability, which results from their high hydrophobicity [ 31 ]. Previous studies have shown that this problem can be solved by using dendrimers as drug carriers [ 32 , 33 ]. In addition, as a result of combining a drug with a dendrimer, an increase in its cytotoxicity is often observed, which allows reducing its dose and, as a result, eliminating many side effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to all metal complexes, especially platinum drugs, they have disadvantages, the most troublesome of which is low bioavailability, which results from their high hydrophobicity [ 31 ]. Previous studies have shown that this problem can be solved by using dendrimers as drug carriers [ 32 , 33 ]. In addition, as a result of combining a drug with a dendrimer, an increase in its cytotoxicity is often observed, which allows reducing its dose and, as a result, eliminating many side effects [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…29–32 The review article of Guo and co-workers highlights the recent advancements in monofunctional platinum( ii ) chemistry. 33…”
Section: Introductionmentioning
confidence: 99%
“…For decades, the search for new antitumor Pt drugs followed the rules established based on knowledge of the mechanism of action of cisplatin and its direct analogs. However, this search is now shifting to the greater structural diversity of platinum complexes, including nonclassical structures [5][6][7][8][9][10][11][12][13][14][15][16]. Cis-Pt(II) iodido complexes have long been predominantly used as intermediates in synthesizing target platinum chlorides and carboxylates, particularly by the Dhara method or its modifications [17,18].…”
Section: Introductionmentioning
confidence: 99%